2018
DOI: 10.3390/environments5110119
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Country Analysis on Energy Savings in Buildings by Means of a Micro-Solar Organic Rankine Cycle System: A Simulation Study

Abstract: In this paper, the smart management of buildings energy use by means of an innovative renewable micro-cogeneration system is investigated. The system consists of a concentrated linear Fresnel reflectors solar field coupled with a phase change material thermal energy storage tank and a 2 kWe/18 kWth organic Rankine cycle (ORC) system. The microsolar ORC was designed to supply both electricity and thermal energy demand to residential dwellings to reduce their primary energy use. In this analysis, the achievable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It was concluded that the turbine expansion ratio increased the ejector cooling system efficiency at a high rate. Arteconi et al [8] used a linear Fresnel collector (LFR) in a micro-scale and solar-powered ORC power plant. In their study, the surface area of the collector, which gives a heat output of 80 kW at a nominal radiation value of 900 W/m 2 , was determined as 146 m 2 .…”
Section: Aims and Scopementioning
confidence: 99%
“…It was concluded that the turbine expansion ratio increased the ejector cooling system efficiency at a high rate. Arteconi et al [8] used a linear Fresnel collector (LFR) in a micro-scale and solar-powered ORC power plant. In their study, the surface area of the collector, which gives a heat output of 80 kW at a nominal radiation value of 900 W/m 2 , was determined as 146 m 2 .…”
Section: Aims and Scopementioning
confidence: 99%
“…At residential level, micro-cogeneration has a very interesting potential [10], and thermal power output from ORC systems can be usefully recovered for domestic hot water or space heating purposes [11]. Given that energy production from solar technologies and user demand are not always simultaneous, thermal energy storage (TES) systems are required to decouple them and usefully extend the operation of solar plants.…”
Section: Introductionmentioning
confidence: 99%